Hypoxia with (18)F-fluoroerythronitroimidazole integrated positron emission tomography and computed tomography ((18)F-FETNIM PET/CT) in locoregionally advanced head and neck cancer: Hypoxia changes during chemoradiotherapy and impact on clinical outcome - Hu, Man (Medicine (Baltimore), 2019)
Hypoxia is a well-recognized biological characteristic to therapy resistance and negative prognostic factor in patients with head and neck squamous cell carcinoma (HNSCC). This study aims to investigate the changes of hypoxia measured by (18)F-fluoroerythronitroimidazole (FETNIM) uptake on integrated positron emission tomography and computed tomography (PET/CT) during chemoradiotherapy and its prognostic value of clinical outcome in locoregionally advanced HNSCC. Thirty-two patients with locoregionally advanced HNSCC who received definitive treatment with concurrent chemoradiotherapy underwent FETNIM PET/CT scans before and after 5 weeks of treatment. The intensity of hypoxia using the maximum standardized uptake value (SUVmax) was evaluated both on primary lesion and metastatic lymph node (MLN). The pre-SUVmax and mid-SUVmax were defined as SUVmax on pre- and mid-FETNIM PET/CT. The local control (LC), regional control (RC), distant metastatic-free survival (DMFS), and overall survival (OS) were collected in patient follow-ups. Mid-SUVmax decreased significantly both in the primary tumor (t = 8.083, P < .001) and MLN (t = 6.808, P < .001) compared to pre-SUVmax. With a median follow-up of 54 months, the 5-year LC, RC, DMFS, and OS rates were 55%, 66.7%, 64.7%, and 55%, respectively, for all of the patients. On univariate analysis, patients with high pre-SUVmax in primary tumor had significantly worse LC (56.3% vs 87.5%, P = .046) and OS (43.8% vs 87.5%, P = .023) than other patients. Patients with high mid-SUVmax had significantly worse DMFS (50% vs 84.6%, P = .049) and OS (33.3% vs 73.1%, P = .028) than other patients. The tumor grade and mid-SUVmax were the significant predictors of OS on multivariate analysis. In this study, hypoxia in tumor significantly decreased during chemoradiotherapy. The persistent hypoxia predicted poor OS. The data provided evidence that FETNIM PET/CT could be used dynamically for selecting appropriate patients and optimal timing of hypoxia-adapted therapeutic regimens.